2012
DOI: 10.1186/1745-6215-13-4
|View full text |Cite
|
Sign up to set email alerts
|

A cost-effectiveness analysis of provider interventions to improve health worker practice in providing treatment for uncomplicated malaria in Cameroon: a study protocol for a randomized controlled trial

Abstract: BackgroundGovernments and donors all over Africa are searching for sustainable, affordable and cost-effective ways to improve the quality of malaria case management. Widespread deficiencies have been reported in the prescribing and counselling practices of health care providers treating febrile patients in both public and private health facilities. Cameroon is no exception with low levels of adherence to national guidelines, the frequent selection of non-recommended antimalarials and the use of incorrect dosag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…A stratified multistage cluster survey was conducted in the two study sites as reported in the study protocol [17]. The quantitative study, carried out through patient exit surveys and clinician/facility surveys, showed that there was over-diagnosis of malaria in health facilities [6] .…”
Section: Methodsmentioning
confidence: 99%
“…A stratified multistage cluster survey was conducted in the two study sites as reported in the study protocol [17]. The quantitative study, carried out through patient exit surveys and clinician/facility surveys, showed that there was over-diagnosis of malaria in health facilities [6] .…”
Section: Methodsmentioning
confidence: 99%
“…Such clinician-oriented interventions have been successful elsewhere when carried out at a local level through participatory workshops (Fonn et al, 2001). We have designed a supporting intervention for providers based on these principles, which will be compared with standard introduction of RDTs in a cluster randomised controlled trial in 2011-12 (clinicaltrials.gov NCT01350752) (Wiseman et al, 2012). Our results also suggest that the role of probabilistic guidelines in routine case management needs to be debated amongst the wider community of clinicians in the professions of medicine and nursing.…”
Section: Enacting Malaria: 'Evidence'mentioning
confidence: 99%
“…This exploratory analysis was undertaken to generate hypotheses and guide the design of interventions to support the roll-out of malaria RDTs with updated clinical guidelines. The effectiveness and cost-effectiveness of the interventions are being evaluated in cluster-randomized trials at selected sites in Cameroon and Nigeria ( Wiseman et al 2012a , b ).…”
Section: Introductionmentioning
confidence: 99%